Reduced Sperm Count and Normal Fertility in Male Mice with Targeted Disruption of the ADP-Ribosylation Factor-Like 4 (Arl4) Gene - Schürmann, A. (American Society for Microbiology, 2002)
The ADP-ribosylation factor-like protein 4 (ARL4) is a 22-kDa GTP-binding protein which is abundant in testes of pubertal and adult rodents but absent in testes from prepubertal animals. During testis development, ARL4 expression starts at day 16 when the spermatogenesis proceeds to the late pachytene. In the adult testis, the ARL4 protein was detected in pre- and postmeiotic cells, spermatocytes, and spermatides, but not in spermatogonia and mature spermatozoa. Mouse Arl4-null mutants generated by targeted disruption of the Arl4 gene were viable and grew normally; male as well as female Arl4(−/−) mice were fertile. However, inactivation of the Arl4 gene resulted in a significant reduction of testis weight and sperm count by 30 and 60%, respectively, without reduction of litter size or frequency. It is suggested that the disruption of Arl4 produces a moderate retardation of germ cell development, possibly at the stage of meiosis.